Determining Indicators of Medical Care Quality in Private Health Institutions - A., Kabilova G. (Academia Open, 2025)
General Background: In recent years, non-state medical institutions have become integral to healthcare delivery systems in Uzbekistan, spurred by national reforms aimed at improving service accessibility and diversity. Specific Background: Despite their growing presence, concerns persist regarding the consistency and safety of services in the non-state sector. Knowledge Gap: Limited empirical data exist comparing the quality of care in public and private health institutions, especially within transitional economies such as Uzbekistan. Aims: This study aims to assess and compare the quality of inpatient and outpatient care between a private clinic (TJS-MED) and a public healthcare facility (Vabkent District Medical Association) in Bukhara region using defined quality indicators. Results: Findings revealed that while the private clinic excelled in service speed and patient comfort, it exhibited notable deficiencies in clinical-pathological diagnostic consistency and fulfillment of medical conditions. Overall, the quality coverage score was 86%, deemed “excellent,” though gaps in physician qualifications and technological application were identified. Novelty: The study introduces a structured indicator-based assessment tool tailored to the Uzbek healthcare context, allowing quantifiable comparisons across sectors. Implications: The results advocate for enhanced regulatory oversight, standardized clinical protocols, and investment in medical personnel training to ensure quality equity across healthcare providers. Highlight : Quality Variability – Non-state clinics often offer faster service but show inconsistency in clinical standards and staff qualifications. Evaluation Tools – A mixed-methods approach using surveys, records, and expert interviews helps assess quality indicators effectively. Policy Implication – There is an urgent need for regulatory reforms and standardized clinical guidelines to ensure patient safety. Keywords : Non-State Medical Institutions, Medical Care Quality, Healthcare Indicators, Patient Satisfaction, Regulatory Oversight